Brand loyalty among Norwegian car owners. (July 2016) - Jørgensen, Finn; Mathisen, Terje Andreas; Pedersen, Hassa
Abstract: Obtaining brand-loyal customers has been demonstrated to be vital for profitability and survival of firms. Loyal customers generally have a higher willingness-to-pay and lower price sensitivity compared to other customers. In this article, we study brand loyalty among car owners using empirical data on 35, 000 car changes in Norway from 1985 to 2013. In contrast to earlier studies on loyalty within this industry that aimed at revealing the attitudes of customers, our data discuss the actual behaviour. As a supplement to our behaviour data set, we use satisfaction measures produced by Autoindex. Average loyalty, as measured by the consecutive purchase of the same brand, amounts to 26.4%. By including returning customers and measuring the repurchase of the same brand as one of the customer's three previous cars, the average loyalty increases to 36.7%. In general, the most prevalent brands attract the most loyal customers. A logit model is applied to describe the factors that have the strongest influence on brand loyalty. The information obtained by this study is of interest to several parts of the automotive industry value chain. Moreover, the analysis is relevant for researchers conducting attitudinal studies on loyalty and satisfaction by comparing this information to the actual behaviour of customers.